Effect of Interactive Book Reading on Speaking Skills of Pre-primary School Children in Ibadan Metropolis in Nigeria - Amosun, Moses Dele; John, Adedamola Olubisi (Papers in Education and Development, 2023)
Speaking skills are essential for play and learning in the classroom, as passing and receiving information are achieved through these skills. However, many children find it difficult to interact using the English language. The study adopted the pre-test and post-test quasi-experimental research design. Forty-one children from two schools were assigned to experimental and control groups in the study. Seven hypotheses and six validated instruments were used and descriptive and inferential statistics were employed for data analysis. There was a significant main effect of treatment on pre-primary school children ' s speaking skills (F (1, 32) =34.95; P<0.05; É³2=0.52).Conclusively, interactive book reading is an effective reading strategy for pre-primary school children. Based on the findings of the study, it was therefore recommended that, pre-school teachers should adopt, inter alia, interactive book reading to improve the quality of preprimary school children ' s speaking skills. Keywords: communication ability, conventional methods, literacy development, self-esteem, home language